Anti-glare film for automobile headlights and preparation process thereof

Nanocomposite particles are prepared by modifying titanium dioxide and introduced into anti-glare coatings to form a composite anti-glare layer with strong chimeric properties, solving the problem of high surface roughness of the existing anti-glare film for automotive lights, and achieving high light transmittance and scratch resistance.

CN116426016BActive Publication Date: 2025-04-15DONGGUAN KASHIBANG FILM MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310222884.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-04-15
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

The surface roughness of the existing anti-glare film for automotive headlights is relatively large, resulting in a decrease in overall light transmittance, a decrease in clarity and light intensity, and also abrasion and scratch resistance, affecting the clarity and anti-glare properties of the headlights during subsequent use.

Method used

通过使用硅烷偶联剂改性二氧化钛,制备纳米复合粒子A和纳米复合粒子B,并将其分别引入防眩光涂料A和防眩光涂料B中,通过控制粒径差和折射率差异,形成嵌合性强的复合防眩光层,降低表面粗糙度,增强耐划痕性和透光率。

Benefits of technology

It achieves the enhancement of light transmittance and scratch resistance on the basis of ensuring anti-glare performance, improves the clarity and light intensity of the car light, and extends the service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of anti-glare films, in particular to an anti-glare film for automobile headlights and a preparation process thereof. The method comprises the following steps: step 1: modifying titanium dioxide with a silane coupling agent to obtain modified titanium dioxide; step 2: (1) coating the surface of the modified titanium dioxide with a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene to obtain nanocomposite particles A; (2) coating the surface of the modified titanium dioxide with a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid and styrene to obtain nanocomposite particles B; step 3: uniformly mixing the nanocomposite particles A and nanocomposite particles B with methyl methacrylate particles and a resin composition to obtain anti-glare coating A and anti-glare coating B; step 4: sequentially coating the anti-glare coating A and the anti-glare coating B on the surface of a PET base film, drying once, UV curing, drying twice, slitting and rolling to obtain an anti-glare film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-glare films, in particular to an anti-glare film for automobile lamps and a preparation process thereof. Background Art

[0002] Headlights are an important tool for vehicles to drive at night. There is a problem of glare pollution when high-brightness headlights are irradiated. Glare pollution will cause uneven brightness in the human field of vision, resulting in visual illusions or temporary blindness, leading to traffic accidents and reducing driving safety. Therefore, it is very necessary for headlights to have anti-glare properties.

[0003] Anti-glare film is a film that uses light scattering properties to diffuse the light emitted by the light source in the lamp while reducing the visual interference of external incident light. Its preparation methods include dry method and wet method. Compared with the dry method, which requires the use of complex equipment, the wet method is simple and low-cost. It only needs to coat the coating material containing inorganic or organic scattering ions on the base film and solidify it; the coating layer can form a concave-convex structure on the surface of the film, thereby producing diffuse reflection, scattering and other phenomena, reducing glare stimulation. In the prior art, in order to enhance the anti-glare effect, the surface roughness of the anti-glare film is relatively large. On the one hand, it will reduce the overall light transmittance, resulting in a decrease in the clarity and light intensity of the headlights. On the other hand, due to the increase in surface roughness, it will reduce the wear resistance and scratch resistance, making the surface of the headlights easy to scratch, reducing the clarity and anti-glare properties of the headlights during subsequent use.

[0004] In summary, it is of great significance to solve the above problems and prepare an anti-glare film for automobile lights. Summary of the invention

[0005] The object of the present invention is to provide an anti-glare film for automobile lamps and a preparation process thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A process for preparing an anti-glare film for automobile lamps comprises the following steps:

[0008] Step 1: using a silane coupling agent to modify titanium dioxide to obtain modified titanium dioxide;

[0009] Step 2: (1) Add modified titanium dioxide and sodium dodecyl sulfate to deionized water in sequence, stir evenly, add sodium persulfate and stir evenly; add a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene dropwise, stir to react, wash and dry to obtain nanocomposite particles A; (2) Add modified titanium dioxide, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether to deionized water in sequence, stir evenly, add sodium persulfate and stir evenly; add a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid and styrene dropwise, stir to react, wash and dry to obtain nanocomposite particles B;

[0010] Step 3: (1) mixing nanocomposite particles A, methyl methacrylate particles and a resin composition uniformly to obtain an anti-glare coating A; (2) mixing nanocomposite particles B, methyl methacrylate particles and a resin composition uniformly to obtain an anti-glare coating B;

[0011] Step 4: coating the anti-glare coating A and the anti-glare coating B on the surface of the PET base film in sequence, drying once, UV curing, and secondary drying to obtain a composite anti-glare layer, slitting, and rolling to obtain an anti-glare film.

[0012] Further, the raw materials of the nanocomposite particles A include the following materials: by mass, 5 to 7 parts of modified titanium dioxide, 0.03 to 0.04 parts of sodium dodecyl sulfate, 50 to 70 parts of deionized water, 1.5 to 1.8 parts of dimethylaminoethyl methacrylate, 1.2 to 1.5 parts of acrylic acid, and 16 to 18 parts of styrene;

[0013] The raw materials of the nanocomposite particles B include the following materials: by mass, 5 to 7 parts of modified titanium dioxide, 0.03 to 0.04 parts of sodium dodecyl sulfate, 0.02 to 0.03 parts of nonylphenol polyoxyethylene ether, 50 to 70 parts of deionized water, 0.8 to 1 parts of methyl methacrylate, 1.1 to 1.4 parts of o-phenylphenoxyethyl acrylate, 0.8 to 0.9 parts of acrylic acid, and 16 to 18 parts of styrene.

[0014] Furthermore, the raw materials of the resin composition include the following materials: by weight, 30 to 40 parts of epoxy acrylate, 20 to 30 parts of polyurethane acrylate, 10 to 12 parts of 1,6-hexanediol diacrylate, 2 to 3 parts of photoinitiator 1173, 1 to 2 parts of photoinitiator 184, 10 to 12 parts of tetrahydrofuran, and 12 to 14 parts of acetone.

[0015] Furthermore, in the anti-glare coating A, the nano-composite particles A account for 2.2-2.5 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 1.5-1.8 wt% of the mass of the resin composition; in the anti-glare coating B, the nano-composite particles B account for 2.7-2.8 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 0.2-0.3 wt% of the mass of the resin composition.

[0016] Furthermore, step 3 includes the following steps: (1) the nanocomposite particles A and nanocomposite particles are modified using sodium hydroxide and hydrochloric acid in sequence to obtain modified nanoparticles A and modified nanoparticles B; (2) the modified nanoparticles A are uniformly mixed with methyl methacrylate particles and a resin composition to obtain an anti-glare coating A; and (3) the modified nanoparticles B are uniformly mixed with methyl methacrylate particles and a resin composition to obtain an anti-glare coating B.

[0017] Furthermore, the preparation process of the modified nanoparticle A is as follows: adding the nanocomposite particles A to deionized water, dispersing them uniformly to obtain a 12-15wt% emulsion, adding deionized water 10 times the volume of the emulsion to dilute it, adding sodium dodecylbenzene sulfonate and butanone to stir uniformly, using sodium hydroxide to adjust the pH to 11.8-12.1, stirring at 85-90°C for 2-3 hours; using hydrochloric acid to adjust the pH to 2.2-2.5, stirring at 85-90°C for 2-3 hours to obtain the modified nanoparticle A; the nanocomposite particles B are modified in the same manner as above to obtain the modified nanoparticle B.

[0018] Furthermore, the preparation process of modified titanium dioxide is as follows: titanium dioxide is added to deionized water, ultrasonically dispersed evenly, hydrochloric acid is added to adjust the pH to 5.8-6.2, silane coupling agent KH-570 is added, stirred at 25-30° C. for 2-3 hours, washed and dried to obtain modified titanium dioxide; wherein the amount of silane coupling agent added accounts for 5-6wt% of titanium dioxide.

[0019] Furthermore, in step 4, the primary drying temperature is 60-65°C, and the secondary drying temperature is 90-100°C; the UV curing process is: under a rod-shaped UV lamp, the light intensity is set to 2.5-3.5 mW / cm 2 The incident angle of the light perpendicular to the PET film is 20-35° parallel to the curing, and the irradiation energy is 80-100mJ / cm 2 .

[0020] Furthermore, the thickness of the PET base film is 80-100 μm, and the coating amount of the anti-glare coating A is 60-80 g / m 2 ; The coating amount of anti-glare coating B is 60-80g / m 2 .

[0021] Furthermore, an anti-glare film is prepared by a preparation process of an anti-glare film for automobile headlights.

[0022] The beneficial effects of this technical solution are as follows:

[0023] In the scheme (1), nano-composite particles A and nano-composite particles B are prepared by coating nano-titanium dioxide in an organic shell layer prepared from acrylate, acrylic acid, and styrene. The particle size difference between nano-composite particles A and nano-composite particles B is controlled by controlling the type and amount of surfactant introduced during the preparation process. The average particle size of nano-composite particles A is 300nm, and the average particle size of nano-composite particles B is 240nm. Therefore, after the two are introduced into anti-glare coating A and anti-glare coating B respectively, the nano-composite particles A with a larger particle size are in the inner layer, and the nano-composite particles B with a smaller particle size are arranged in the outer layer, so that the two have better intercalation, can reduce the surface roughness, and thus enhance the surface scratch resistance.

[0024] In addition, in the scheme, the refractive index difference between nanocomposite particles A and nanocomposite particles B is regulated by controlling the type of acrylate introduced and the amount of acrylic acid introduced. Specifically: dimethylaminoethyl methacrylate is introduced into nanocomposite particle A, and its refractive index is about 1.43; and o-phenylphenoxyethyl acrylate is introduced into nanocomposite particle B, and its refractive index is about 1.57. On the other hand, in the further modification process, different amounts of acrylic acid are introduced, resulting in different porosities. Since the refractive index shows a downward trend with the increase of porosity, the refractive index difference between the two particles is further increased by utilizing the porosity difference. In this way, the two particles are introduced into anti-glare coating A and anti-glare coating B respectively, and the different refractive indices generated between the coatings are utilized to produce anti-reflection, thereby enhancing the anti-glare performance. On the other hand, the subsequent porous modification enhances the light transmittance while ensuring the anti-glare property, which can enhance the clarity and intensity of the internal light source.

[0025] In addition, the scheme further introduces micron-sized polymethyl methacrylate particles to assist the two nanoparticles in forming a concave-convex structure on the surface to enhance the anti-glare property.

[0026] In the (2) scheme, since there are differences in refractive index, reactivity and molecular mobility between nanocomposite particles A and nanocomposite particles B, the curing light source medium is limited to a rod-shaped medium during the photocuring process, and the incident angle of the light source is set. The purpose is to enhance the orderliness of the medium inside the anti-glare layer, thereby controlling the internal distribution structure and improving the internal anisotropy. Without reducing the light intensity, the anti-glare property and light transmittance are enhanced, thereby ensuring the clarity of the headlight light source.

[0027] (3) In the scheme, although the introduction of polymethyl methacrylate particles can enhance the anti-glare property, it will reduce the hardness of the anti-glare layer. Therefore, in the scheme, the resin composition uses epoxy acrylate containing rigid benzene rings to enhance the surface hardness and thermal stability of the anti-glare layer. Because the rigidity of a single epoxy resin acrylate is too large, the scheme introduces polyurethane acrylate with better flexibility, which has better adhesion. The two have good compatibility and form an interlaced network, which enhances the tensile strength and scratch resistance of the anti-glare layer. In addition, a lower content of polymethyl methacrylate is introduced into the outer layer, and a higher content of nanocomposite particles B is added. First, the introduction of nanoparticles can play a role in rigid chain breaking and enhance the surface scratch resistance. Second, it can reduce residual stress, thereby improving the tensile strength and scratch resistance of the anti-glare layer. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Embodiment 1:

[0030] Step 1: Add nano titanium dioxide to deionized water, disperse it evenly by ultrasonication, add hydrochloric acid to adjust the pH to 6, add silane coupling agent KH-570, stir at 30°C for 2 hours, wash and dry to obtain modified titanium dioxide; wherein the amount of silane coupling agent added accounts for 6wt% of the nano titanium dioxide.

[0031] Step 2: (1) adding modified titanium dioxide and sodium dodecyl sulfate to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles A; adding nanocomposite particles A to deionized water, dispersing evenly to obtain a 15 wt % emulsion, adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate (accounting for 5 wt % of the mass of nanocomposite particles A) and butanone (accounting for 2.5 wt % of the mass of nanocomposite particles A) and stirring evenly, adjusting the pH to 11.1 with sodium hydroxide, stirring at 90° C. for 3 hours; adjusting the pH to 2.4 with hydrochloric acid, stirring at 90° C. for 3 hours to obtain modified nanoparticles A;

[0032] Among them, by mass, it includes 6 parts of modified titanium dioxide, 0.04 parts of sodium dodecyl sulfate, 60 parts of deionized water, 1.6 parts of dimethylaminoethyl methacrylate, 1.4 parts of acrylic acid, and 17 parts of styrene;

[0033] (2) adding modified titanium dioxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid, and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles B; adding nanocomposite particles B to deionized water, dispersing evenly to obtain a 15 wt % emulsion, adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate (accounting for 5 wt % of the mass of nanocomposite particles B) and butanone (accounting for 2.5 wt % of the mass of nanocomposite particles B) and stirring evenly, adjusting the pH to 11.0 with sodium hydroxide, stirring at 90° C. for 3 hours; adjusting the pH to 2.3 with hydrochloric acid, stirring at 90° C. for 3 hours to obtain modified nanoparticles B;

[0034] Among them, calculated by mass, it includes 6 parts of modified titanium dioxide, 0.04 parts of sodium dodecyl sulfate, 0.03 parts of nonylphenol polyoxyethylene ether, 60 parts of deionized water, 1 part of methyl methacrylate, 1.2 parts of o-phenylphenoxyethyl acrylate, 0.8 parts of acrylic acid, and 17 parts of styrene.

[0035] Step 3: (1) uniformly mixing the modified nanoparticles A, methyl methacrylate particles and a resin composition to obtain an anti-glare coating A; wherein the modified nanoparticles A account for 2.4 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 1.6 wt% of the mass of the resin composition;

[0036] (2) The modified nanoparticles B, methyl methacrylate particles and a resin composition are uniformly mixed to obtain an anti-glare coating B; wherein the modified nanoparticles B account for 2.8 wt % of the resin composition, and the methyl methacrylate particles account for 0.2 wt % of the resin composition.

[0037] The raw materials of the resin composition include the following materials: by weight, 35 parts of epoxy acrylate, 25 parts of polyurethane acrylate, 12 parts of 1,6-hexanediol diacrylate, 2.5 parts of photoinitiator 1173, 1.5 parts of photoinitiator 184, 10 parts of tetrahydrofuran, and 14 parts of acetone.

[0038] Step 4: Spray anti-glare coating A and anti-glare coating B on the surface of the PET base film in sequence, dry at 60°C for 2 hours, and set the light intensity to 3mW / cm under a rod-shaped UV lamp. 2 The incident angle of the light perpendicular to the PET film is 30° parallel to the UV curing, and the irradiation energy is 100mJ / cm 2 ; secondary drying at 95°C for 2 hours to obtain a composite anti-glare layer, slitting and rolling to obtain an anti-glare film.

[0039] Embodiment 2:

[0040] Step 1: Add nano titanium dioxide to deionized water, disperse it evenly by ultrasonication, add hydrochloric acid to adjust the pH to 6, add silane coupling agent KH-570, stir at 30°C for 2 hours, wash and dry to obtain modified titanium dioxide; wherein the amount of silane coupling agent added accounts for 6wt% of the nano titanium dioxide.

[0041] Step 2: (1) adding modified titanium dioxide and sodium dodecyl sulfate to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles A; adding nanocomposite particles A to deionized water, dispersing evenly to obtain a 15 wt % emulsion, adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate (accounting for 5 wt % of the mass of nanocomposite particles A) and butanone (accounting for 2.5 wt % of the mass of nanocomposite particles A) and stirring evenly, adjusting the pH to 11.1 with sodium hydroxide, stirring at 90° C. for 3 hours; adjusting the pH to 2.4 with hydrochloric acid, stirring at 90° C. for 3 hours to obtain modified nanoparticles A;

[0042] Among them, by mass, it includes 5 parts of modified titanium dioxide, 0.03 parts of sodium dodecyl sulfate, 50 parts of deionized water, 1.5 parts of dimethylaminoethyl methacrylate, 1.5 parts of acrylic acid, and 17 parts of styrene;

[0043] (2) adding modified titanium dioxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid, and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles B; adding nanocomposite particles B to deionized water, dispersing evenly to obtain a 15 wt % emulsion, adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate (accounting for 5 wt % of the mass of nanocomposite particles B) and butanone (accounting for 2.5 wt % of the mass of nanocomposite particles B) and stirring evenly, adjusting the pH to 11.0 with sodium hydroxide, stirring at 90° C. for 3 hours; adjusting the pH to 2.3 with hydrochloric acid, stirring at 90° C. for 3 hours to obtain modified nanoparticles B;

[0044] Among them, calculated by mass, it includes 5 parts of modified titanium dioxide, 0.03 parts of sodium dodecyl sulfate, 0.02 parts of nonylphenol polyoxyethylene ether, 50 parts of deionized water, 0.8 parts of methyl methacrylate, 1.4 parts of o-phenylphenoxyethyl acrylate, 0.8 parts of acrylic acid, and 17 parts of styrene.

[0045] Step 3: (1) uniformly mixing the modified nanoparticles A, methyl methacrylate particles and a resin composition to obtain an anti-glare coating A; wherein the modified nanoparticles A account for 2.2 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 1.8 wt% of the mass of the resin composition;

[0046] (2) The modified nanoparticles B, methyl methacrylate particles and a resin composition are uniformly mixed to obtain an anti-glare coating B; wherein the modified nanoparticles B account for 2.8 wt % of the resin composition, and the methyl methacrylate particles account for 0.2 wt % of the resin composition.

[0047] The raw materials of the resin composition include the following materials: by weight, 30 parts of epoxy acrylate, 30 parts of polyurethane acrylate, 12 parts of 1,6-hexanediol diacrylate, 2 parts of photoinitiator 1173, 2 parts of photoinitiator 184, 12 parts of tetrahydrofuran, and 12 parts of acetone.

[0048] Step 4: Spray anti-glare coating A and anti-glare coating B on the surface of the PET base film in sequence, dry at 60°C for 2 hours, and set the light intensity to 3.5mW / cm under a rod-shaped UV lamp. 2 The incident angle of the light to the PET film is 35° parallel to the UV curing, and the irradiation energy is 80mJ / cm 2 ; secondary drying at 95°C for 2 hours to obtain a composite anti-glare layer, slitting and rolling to obtain an anti-glare film.

[0049] Embodiment 3:

[0050] Step 1: Add nano titanium dioxide to deionized water, disperse it evenly by ultrasonication, add hydrochloric acid to adjust the pH to 6, add silane coupling agent KH-570, stir at 30°C for 2 hours, wash and dry to obtain modified titanium dioxide; wherein the amount of silane coupling agent added accounts for 6wt% of the nano titanium dioxide.

[0051] Step 2: (1) adding modified titanium dioxide and sodium dodecyl sulfate to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles A; adding nanocomposite particles A to deionized water, dispersing evenly to obtain a 15 wt % emulsion, adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate (accounting for 5 wt % of the mass of nanocomposite particles A) and butanone (accounting for 2.5 wt % of the mass of nanocomposite particles A) and stirring evenly, adjusting the pH to 11.1 with sodium hydroxide, stirring at 90° C. for 3 hours; adjusting the pH to 2.4 with hydrochloric acid, stirring at 90° C. for 3 hours to obtain modified nanoparticles A;

[0052] Among them, by mass, it includes 7 parts of modified titanium dioxide, 0.04 parts of sodium dodecyl sulfate, 70 parts of deionized water, 1.8 parts of dimethylaminoethyl methacrylate, 1.2 parts of acrylic acid, and 17 parts of styrene;

[0053] (2) adding modified titanium dioxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid, and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles B; adding nanocomposite particles B to deionized water, dispersing evenly to obtain a 15 wt % emulsion, adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate (accounting for 5 wt % of the mass of nanocomposite particles B) and butanone (accounting for 2.5 wt % of the mass of nanocomposite particles B) and stirring evenly, adjusting the pH to 11.0 with sodium hydroxide, stirring at 90° C. for 3 hours; adjusting the pH to 2.3 with hydrochloric acid, stirring at 90° C. for 3 hours to obtain modified nanoparticles B;

[0054] Among them, calculated by mass, it includes 7 parts of modified titanium dioxide, 0.04 parts of sodium dodecyl sulfate, 0.03 parts of nonylphenol polyoxyethylene ether, 70 parts of deionized water, 1 part of methyl methacrylate, 1.1 parts of o-phenylphenoxyethyl acrylate, 0.9 parts of acrylic acid, and 17 parts of styrene.

[0055] Step 3: (1) uniformly mixing the modified nanoparticles A, methyl methacrylate particles and a resin composition to obtain an anti-glare coating A; wherein the modified nanoparticles A account for 2.5 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 1.5 wt% of the mass of the resin composition;

[0056] (2) The modified nanoparticles B, methyl methacrylate particles and a resin composition are uniformly mixed to obtain an anti-glare coating B; wherein the modified nanoparticles B account for 2.7 wt % of the resin composition, and the methyl methacrylate particles account for 0.3 wt % of the resin composition.

[0057] The raw materials of the resin composition include the following materials: by weight, 40 parts of epoxy acrylate, 20 parts of polyurethane acrylate, 10 parts of 1,6-hexanediol diacrylate, 3 parts of photoinitiator 1173, 1 part of photoinitiator 184, 12 parts of tetrahydrofuran, and 14 parts of acetone.

[0058] Step 4: Spray anti-glare coating A and anti-glare coating B on the surface of the PET base film in sequence, dry at 60°C for 2 hours, and set the light intensity to 2.5mW / cm under a rod-shaped UV lamp. 2The incident angle of the light perpendicular to the PET film is 20° parallel to the UV curing, and the irradiation energy is 100mJ / cm 2 ; secondary drying at 95°C for 2 hours to obtain a composite anti-glare layer, slitting and rolling to obtain an anti-glare film.

[0059] Embodiment 4:

[0060] Step 1: Add nano titanium dioxide to deionized water, disperse it evenly by ultrasonication, add hydrochloric acid to adjust the pH to 6, add silane coupling agent KH-570, stir at 30°C for 2 hours, wash and dry to obtain modified titanium dioxide; wherein the amount of silane coupling agent added accounts for 6wt% of the nano titanium dioxide.

[0061] Step 2: (1) adding modified titanium dioxide and sodium dodecyl sulfate to deionized water in sequence, stirring evenly, adding sodium persulfate and stirring evenly; adding a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene dropwise, stirring for reaction, washing and drying to obtain nanocomposite particles A; wherein, by weight, the mixture comprises 6 parts of modified titanium dioxide, 0.04 parts of sodium dodecyl sulfate, 60 parts of deionized water, 1.6 parts of dimethylaminoethyl methacrylate, 1.4 parts of acrylic acid and 17 parts of styrene;

[0062] (2) Add modified titanium dioxide, sodium dodecyl sulfate, and nonylphenol polyoxyethylene ether to deionized water in sequence, stir evenly, add sodium persulfate and stir evenly; add dropwise a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid, and styrene, stir for reaction, wash and dry to obtain nanocomposite particles B; wherein, by mass, the mixture includes 6 parts of modified titanium dioxide, 0.04 parts of sodium dodecyl sulfate, 0.03 parts of nonylphenol polyoxyethylene ether, 60 parts of deionized water, 1 part of methyl methacrylate, 1.2 parts of o-phenylphenoxyethyl acrylate, 0.8 parts of acrylic acid, and 17 parts of styrene.

[0063] Step 3: (1) mixing nanocomposite particles A, methyl methacrylate particles and a resin composition to obtain an anti-glare coating A; wherein the nanocomposite particles A account for 2.4 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 1.6 wt% of the mass of the resin composition;

[0064] (2) The nanocomposite particles B, methyl methacrylate particles and a resin composition are uniformly mixed to obtain an anti-glare coating B; wherein the nanocomposite particles B account for 2.8 wt % of the resin composition, and the methyl methacrylate particles account for 0.2 wt % of the resin composition.

[0065] The raw materials of the resin composition include the following materials: by weight, 35 parts of epoxy acrylate, 25 parts of polyurethane acrylate, 12 parts of 1,6-hexanediol diacrylate, 2.5 parts of photoinitiator 1173, 1.5 parts of photoinitiator 184, 10 parts of tetrahydrofuran, and 14 parts of acetone.

[0066] Step 4: Spray anti-glare coating A and anti-glare coating B on the surface of the PET base film in sequence, dry at 60°C for 2 hours, and set the light intensity to 3mW / cm under a rod-shaped UV lamp. 2 The incident angle of the light perpendicular to the PET film is 30° parallel to the UV curing, and the irradiation energy is 100mJ / cm 2 ; secondary drying at 95°C for 2 hours to obtain a composite anti-glare layer, slitting and rolling to obtain an anti-glare film.

[0067] Comparative Example 1: Modified nanoparticle B is not introduced; modified nanoparticle B is replaced by modified nanoparticle A, and the rest is the same as Example 1;

[0068] Comparative Example 2: Dimethylaminoethyl methacrylate in the nanocomposite particles A and o-phenylphenoxyethyl acrylate in the nanocomposite particles B were replaced with methyl methacrylate, and the rest was the same as in Example 1;

[0069] Comparative Example 3: The content of the anti-glare coating B was changed, the modified nanoparticles B accounted for 1.8wt% of the mass of the resin composition, and the methyl methacrylate particles accounted for 1.2wt% of the mass of the resin composition; the rest was the same as in Example 1;

[0070] Comparative Example 4: A rectangular UV lamp was used as a light source, the incident angle was not set, and the light curing was fixed. The rest was the same as in Example 1.

[0071] In the above embodiments, the average particle size of nano-titanium dioxide is 25 nm, and the manufacturer is Aladdin; the average particle size of polymethyl methacrylate microspheres is 5 μm, and the manufacturer is Lucky Company; the manufacturer of silane coupling agent KH570 is Sigma-Aldrich; the CAS number of dimethylaminoethyl methacrylate is 2867-47-2, and the manufacturer is Sigma-Aldrich; the CAS number of acrylic acid is 79-10-7, and the manufacturer is Sigma-Aldrich; the CAS number of styrene is 100-42-5, and the manufacturer is Sigma-Aldrich; the CAS number of o-phenylphenoxyethyl acrylate is 9144 2-42-9, manufacturer is Alpha; CAS number of methyl methacrylate is 80-62-6, manufacturer is Sigma-Aldrich; CAS number of sodium dodecyl sulfate and nonylphenol polyoxyethylene ether is 14409-72-4, manufacturer is Changzhou Junxin Plastic Chemical Co., Ltd., CAS number of epoxy acrylate is 71281-65-7, manufacturer is Sigma-Aldrich; the product number of polyurethane acrylate is SWE2200, manufacturer is Guangzhou Sanwang Chemical Materials Co., Ltd.; CAS number of 1,6-hexanediol diacrylate is 13048-33-4, manufacturer is Sigma-Aldrich. The thickness of the PET base film is 80μm, and it is pre-cleaned with acetone before spraying. The coating amount of anti-glare coating A is 75g / m 2 , the coating amount of anti-glare coating B is 75g / m 2 .

[0072] Experiment: The anti-glare films prepared in the above examples and comparative examples were used as samples, and the transmittance haze of the samples was tested using a transmittance haze meter in accordance with the national standard GB / T2410-80; the surface hardness was tested by the coating hardness pencil test method in accordance with the national standard GB / T6769; the tensile strength of the anti-glare films was tested using a universal mechanical testing machine at a tensile rate of 100 mm / min in accordance with the national standard GB / T1040.1. All data are shown below:

[0073] sample Light transmittance / % Haze / % Surface hardness Tensile strength / MPa Example 1 91.8 16.3 4H 16.5 Example 2 92.5 15.9 4H 16.1 Example 3 92.9 15.7 4H 16.2 Example 4 85.2 15.2 4H 15.4 Comparative Example 1 88.2 15.5 3H 14.9 Comparative Example 2 92.1 14.4 4H 15.2 Comparative Example 3 87.6 15.6 3H 14.1 Comparative Example 4 84.3 14.6 4H 16.3

[0074] Conclusion: The data in the above table show that the anti-glare film prepared by this scheme has excellent light transmittance, anti-glare, scratch resistance and tensile strength. Comparing the data of Example 4 with the data of Example 1, it is shown that further improving the porosity of the nanocomposite particles can further enhance the light transmittance and anti-glare properties. Comparing the data of Comparative Examples 1 to 5 with the data of Example 1, it is shown that in Comparative Example 1, the surface hardness and tensile strength are reduced due to the single use of modified nanoparticles A; in Comparative Example 2, the anti-glare property is reduced and the mechanical properties are reduced due to the lack of introduction of acrylates with different refractive indices; in Comparative Example 3, the surface wear resistance and light transmittance are reduced due to the change in the content of particles introduced on the surface; in Comparative Example 5, the internal orderliness is reduced and the anti-glare performance is reduced due to the failure to set the mobile UV curing mode.

[0075] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A process for preparing an anti-glare film for automobile lamps, characterized in that: The following steps are involved: Step 1: using a silane coupling agent to modify nano titanium dioxide to obtain modified titanium dioxide; Step 2: (1) Add modified titanium dioxide and sodium dodecyl sulfate to deionized water in sequence, stir evenly, add sodium persulfate and stir evenly; add a mixture of dimethylaminoethyl methacrylate, acrylic acid and styrene dropwise, stir to react, wash and dry to obtain nanocomposite particles A; (2) Add modified titanium dioxide, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether to deionized water in sequence, stir evenly, add sodium persulfate and stir evenly; add a mixture of methyl methacrylate, o-phenylphenoxyethyl acrylate, acrylic acid and styrene dropwise, stir to react, wash and dry to obtain nanocomposite particles B; Step 3: (1) mixing nanocomposite particles A, methyl methacrylate particles and a resin composition uniformly to obtain an anti-glare coating A; (2) mixing nanocomposite particles B, methyl methacrylate particles and a resin composition uniformly to obtain an anti-glare coating B; Step 4: coating the anti-glare coating A and the anti-glare coating B on the surface of the PET base film in sequence and drying them once; UV curing: The UV curing process is as follows: Under a rod-shaped UV lamp, set the light intensity to 2.5-3.5 mW / cm 2 The incident angle of the light perpendicular to the PET film is 20-35° parallel to the curing, and the irradiation energy is 80-100mJ / cm 2 ; Secondary drying to obtain a composite anti-glare layer, slitting and rolling to obtain an anti-glare film; The raw materials of the nanocomposite particles A include the following materials: by weight, 5 to 7 parts of modified titanium dioxide, 0.03 to 0.04 parts of sodium dodecyl sulfate, 50 to 70 parts of deionized water, 1.5 to 1.8 parts of dimethylaminoethyl methacrylate, 1.2 to 1.5 parts of acrylic acid, and 16 to 18 parts of styrene; The raw materials of the nanocomposite particles B include the following materials: by mass, 5 to 7 parts of modified titanium dioxide, 0.03 to 0.04 parts of sodium lauryl sulfate, 0.02 to 0.03 parts of nonylphenol polyoxyethylene ether, 50 to 70 parts of deionized water, 0.8 to 1 parts of methyl methacrylate, 1.1 to 1.4 parts of o-phenylphenoxyethyl acrylate, 0.8 to 0.9 parts of acrylic acid, and 16 to 18 parts of styrene; The raw materials of the resin composition include the following materials: by weight, 30 to 40 parts of epoxy acrylate containing a rigid benzene ring, 20 to 30 parts of polyurethane acrylate, 10 to 12 parts of 1,6-hexanediol diacrylate, 2 to 3 parts of photoinitiator 1173, 1 to 2 parts of photoinitiator 184, 10 to 12 parts of tetrahydrofuran, and 12 to 14 parts of acetone; In the anti-glare coating A, the nanocomposite particles A account for 2.2-2.5 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 1.5-1.8 wt% of the mass of the resin composition; in the anti-glare coating B, the nanocomposite particles B account for 2.7-2.8 wt% of the mass of the resin composition, and the methyl methacrylate particles account for 0.2-0.3 wt% of the mass of the resin composition.

2. The process for preparing an anti-glare film for automobile lamps according to claim 1, characterized in that: Step 3 includes the following steps: (1) the nanocomposite particles A and the nanocomposite particles B are modified using sodium hydroxide and hydrochloric acid in turn to obtain modified nanoparticles A and modified nanoparticles B; (2) the modified nanoparticles A are uniformly mixed with methyl methacrylate particles and a resin composition to obtain an anti-glare coating A; and (3) the modified nanoparticles B are uniformly mixed with methyl methacrylate particles and a resin composition to obtain an anti-glare coating B.

3. The process for preparing an anti-glare film for automobile lamps according to claim 2, characterized in that: The preparation process of modified nanoparticle A is as follows: adding nanocomposite particles A into deionized water, dispersing uniformly to obtain an emulsion of 12-15wt%, then adding deionized water 10 times the volume of the emulsion for dilution, adding sodium dodecylbenzene sulfonate and butanone and stirring uniformly, using sodium hydroxide to adjust the pH to 11.8-12.1, stirring at 85-90°C for 2-3 hours; using hydrochloric acid to adjust the pH to 2.2-2.5, stirring at 85-90°C for 2-3 hours to obtain modified nanoparticle A; nanocomposite particles B are modified in the same manner as above to obtain modified nanoparticle B.

4. The process for preparing an anti-glare film for automobile lamps according to claim 1, characterized in that: The preparation process of modified titanium dioxide is as follows: adding nano titanium dioxide into deionized water, uniformly dispersing by ultrasonication, adding hydrochloric acid to adjust the pH value to 5.8-6.2, adding silane coupling agent KH-570, stirring at 25-30° C. for 2-3 hours, washing and drying to obtain modified titanium dioxide; wherein the amount of the silane coupling agent added accounts for 5-6wt% of the nano titanium dioxide.

5. The process for preparing an anti-glare film for automobile lamps according to claim 1, characterized in that: In step 4, the primary drying temperature is 60-65°C, and the secondary drying temperature is 90-100°C.

6. The process for preparing an anti-glare film for automobile lamps according to claim 1, characterized in that: The thickness of the PET base film is 80-100 μm, and the coating amount of the anti-glare coating A is 60-80 g / m 2 ; The coating amount of anti-glare coating B is 60-80g / m 2 .

7. The anti-glare film prepared according to the process for preparing an anti-glare film for automobile lamps according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Antidazzle, light-transmitting hard coat film

    CN101680972A

  • Anti-dazzle coating and anti-dazzle hardening film

    CN104817951A